Devotees performing aarti in the temple - Mumbai Archive Project Team (Jio Institute, 2024)
Aarti (the waving of a flame, usually from a lit lamp, before a deity during prayers) is accompanied by the ringing of bells, the chanting of mantras, and the distribution of prasad (blessed food) among the devotees.